Comparative study of intra-urban target performance on simulated WorldView-2 and WorldView-3 responses from hyperspectral data - Azevedo, S. C. [UNESP]; Cardim, G. P. [UNESP]; Pedrosa, M. M. [UNESP]; Alcântara, E. H. [UNESP]; Silva, E. A. [UNESP] (My University, 2016)
Urban areas are characterized by high heterogeneity of natural and artificial targets. The hyperspectral data has shown the potential use in urban applications due to discrimination capability of a variety of features. At the same time, the evolution of multispectral sensors is supporting these innovations through improvement of spatial and spectral resolution. This study aims to compare and evaluate the responses simulated for two multispectral satellite WorldView series. Experimental results show that responses simulated for WorldView-3 were consistent with the hyperspectral data. This indicates that the WV-3 simulation results are promising and that improvements incorporated in this sensor, launched last year, will be able to discriminate urban features.